Analisis Persepsi Wajib Pajak Pelaku UMKM Terhadap Penerapan Peraturan Pemerintah Nomor 55 Tahun 2022 di KPP Pratama Makassar Barat - S, Rahmatia; Ka, Veronika Sari Den; Arifin, Rukminih (SUSTAINABLE, 2024)
The government issued policy PP Number 55 of 2022 concerning adjustments to regulations in the field of income tax with a rate of 0.5% imposed on UMKM that have a gross turnover of more than IDR 500 million, to replace PP Number 23 of 2018 with a rate of 0.5% imposed on UMKM that have a gross turnover of less than IDR 500 million. The aim of this research is to analyze and provide an overview of the perceptions of UMKM taxpayers regarding the implementation of PP Number 55 of 2022 at KPP Pratama West Makassar in terms of tax rates, tax sanctions, tax convenience and socialization of PP Number 55 of 2022. This research is descriptive research with a quantitative approach that describes the perceptions of UMKM taxpayers regarding the implementation of PP Number 55 of 2022. Data analysis techniques use validity tests, reliability tests and descriptive data analysis. The results of the research show that the perception of UMKM taxpayers regarding Government Regulation Number 55 of 2022 in terms of tariffs, sanctions, convenience and overall tax socialization is good, and has provided understanding and convenience in paying taxes for UMKM actors.